Structural and Kinematic Analysis of Gear and Lever Differential Mechanisms by Symmetric Movement of Rotation Centers for Driving and Slave Gear Wheels - Sh.P. , Alimukhamedov; A. , Abdukarimov; H.A. , Sharifhodjaeva; K.J. , Rustamov (International Journal of Psychosocial Rehabilitation, 2020)
The article presents a methodology for structural and kinematic analysis of gear-lever differential mechanisms by symmetric movement of the centers of rotation of the driving and driven gears with parallel contours. The degree of mobility of the differential mechanism is determined taking into account excess connections. Expressions are derived for analogues of angular velocities and angular accelerations of links of the gear mechanism, as well as linear velocities and accelerations of the linkage.